A Review On Current Approaches In Floating Drug Delivery System - Gupta, Akanksha; Sharma, Natasha; Khinchi, M. P.; Agrawal, Dilip (Asian Journal of Pharmaceutical Research and Development, 2013)
Floating drug delivery system provides local delivery to specific region like stomach and proximal small intestine and it’s also shows better bioavailability and improved therapeutic activity and substantial benefits to patients. The objective of our review is to compile the recent advancements and literatures regarding the novel do form i.e. the floating drug delivery systems (FDDS) that can be retained in the stomach for a prolonged period of time and gives therapeutic action in a predetermined manner. Gastric emptying is a complex process and makes in vivo performance of the drug delivery systems uncertain. The floating drug delivery systems are useful approach to avoid this variability with increase the retention time of the drug delivery systems for more than 12 hours. Effervescent and non-effervescent are two class of floating system and can formulate either in single unit dosage form or in multiple unit dosage form. The methodologies used in the development of FDDS by formulating effervescent and non effervescent floating tablets based on buoyancy mechanism. By utilizing above feasible approaches it is possible to deliver drugs which have narrow therapeutic window. Our review article suggests that how the gastro retentive dosage forms (GRDFs) help to improve patient compliance and robustness.